2004
DOI: 10.1039/b316105f
|View full text |Cite
|
Sign up to set email alerts
|

Novel chiral liquid crystal with two chiral butyl lactate chains exhibiting several frustrated mesophases including smectic Q and TGB phases separated by an optically isotropic phase

Abstract: A novel symmetric liquid crystalline compound with two chiral butyl lactate chains, (S,S)-bis[4-(1butoxycarbonyl)ethyloxycarbonyltolanyl]fumarate (BisBLOCTF), was synthesized. This compound was found to exhibit a very unusual phase sequence involving several frustrated mesophases, namely smectic Q, TGBC, TGBA and blue phases. In addition, an ''optically isotropic'' phase occurs between the smectic Q and the SmC*, and TGB phases. The different phases were studied by optical observation, DSC, X-ray diffraction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…From a molecular structure viewpoint, the characteristics of the chiral part of the azo‐dichiral molecule are important because all known compounds exhibiting the SmQ phase typically have the same chiral part structure,22–24,30–34 such as that of compounds 17 (Fig. 2), 18 , and 19 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…From a molecular structure viewpoint, the characteristics of the chiral part of the azo‐dichiral molecule are important because all known compounds exhibiting the SmQ phase typically have the same chiral part structure,22–24,30–34 such as that of compounds 17 (Fig. 2), 18 , and 19 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The anomalies detected at the TGBA-TGBC phase transition are slightly higher than the characteristic values usually found. Nevertheless, some compounds have been reported with comparable high enthalpy values at this phase transition [23,24]. The phase transition between the TGBC and SmC* phases exhibits a strong hysteresis.…”
Section: Mesomorphic Propertiesmentioning
confidence: 98%
“…A rare re-entrant ferroelectric phase and the ferroelectric hexatic phase have been found in some of these materials (4). Additionally, the presence of the second and third lactate units in such a molecule leads to a decrease of the phase transition temperatures in comparison with an analogous molecule with only one lactate group (2,3). A very broad SmC* phase was found in materials with a molecular core possessing one biphenyl moiety substituted by chlorine, two more aromatic rings connected by the ester linkage and a chiral part containing one lactate group (5).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, it has been found that materials with three phenyl rings in their molecular core and a chiral part based on the lactate unit possess a ferroelectric chiral smectic C (SmC*) phase (1)(2)(3) and, in the case of two lactate units, a tendency to form the antiferroelectric chiral smectic C (SmC A *) phase has been discovered (2,4). A rare re-entrant ferroelectric phase and the ferroelectric hexatic phase have been found in some of these materials (4).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation